Pengaruh Keputusan Pendanaan Terhadap Likuiditas, Aktivitas Dan Kemampulabaan - Ramadhan, Iqbal Akbar; Sari, Ratih Puspita (Jurnal Ilmiah Manajemen Kesatuan, 2014)
Financial structure is how companies fund their assets. By using funds derived from sources of debts, the management company must be able to well manage their obligations, thus the company will be able to maximize its activities and increase their profitability. Corporate activity is the utilization of all the resources available to produce goods and services while profitability is the company's ability to generate earnings and the potentials to earn income. Increase in activites and profitability will logically increase its earning as well. This will definitely be affecting the liquidity of the company itself. The purpose of this study is to determine how funding decisions taken by the management influence liquidity ratios, activity ratios and profitability ratios. Evaluation is conducted to detemine whether funding decisions taken by the management offund assets are appropriate and having positive effect on ratios of liquidity, activity and profitability. Keyword: debt to equity ratio, quick ratio, total asset turn over, basic eaming power, retum on equity.